Pengaruh Efisiensi Modal Kerja, Solvabilitas Dan Pertumbuhan Penjualan Terhadap Profitabilitas Perusahaan Manufaktur Yang Terdaftar Di Bei Pada Tahun 2015-2019 - Jeremy Alfa Nugraha; Robert Halim; Yulius Jogi Christiawan (Business Accounting Review, 2020)
Research on Working capital efficiency has been performed on but has not shown consistent results. Sample used on this research are manufacturing companies listed at Indonesia Stock Exchange (IDX) on period 2015-2019. This research using Return On Assets (ROA) to measure profitability, while Working Capital Turnover is used to measure working capital efficiency. This research also using solvability and sales growth as controlling variables. Sample data which consist of 88 listed companies across period of 2015-2019, measured up to 440 data. This research resulted in no significant effect from working capital efficiency to profitability. Control variable solvability gave significantly negative effect to profitability, while sales growth gave significantly positive effect to profitability.